2020
DOI: 10.3389/fpsyt.2020.552532
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification for Bipolar Disorder Using Polygenic Risk Scores Among Young High-Risk Adults

Abstract: Identifying high-risk groups with an increased genetic liability for bipolar disorder (BD) will provide insights into the etiology of BD and contribute to early detection of BD. We used the BD polygenic risk score (PRS) derived from BD genome-wide association studies (GWAS) to explore how such genetic risk manifests in young, high-risk adults. We postulated that BD-PRS would be associated with risk factors for BD. Methods: A final sample of 185 young, high-risk German adults (aged 18-35 years) were grouped int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The conversion rate of our study was 12.7%, similar to a prospective cohort study which showed the rate of conversion from MDD to BD in 3 years was 12.4% ( 35 ). The conversion rates have been reported as between 2.5 and 15.4% in follow-up intervals of 3–9 years ( 37 ). The conversion rate of our study was consistent with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The conversion rate of our study was 12.7%, similar to a prospective cohort study which showed the rate of conversion from MDD to BD in 3 years was 12.4% ( 35 ). The conversion rates have been reported as between 2.5 and 15.4% in follow-up intervals of 3–9 years ( 37 ). The conversion rate of our study was consistent with these studies.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Biere’s research confirmed that increased BD-PRS are significant predictive factors for major depressive disorde and attention-deficit hyperactivity disorder (ADHD). 15 These studies support the existence of shared risks between other mental disorders and BD, and increasing our understanding of the underlying genetic characteristics of these phenotypes can aid in early disease identification and risk stratification. David et al indicated that BD and SCZ PRSs provide a moderate level of independent differentiation between BD and MDD cases, suggesting that PRS for psychiatric disorders can somewhat differentiate between the two diseases.…”
Section: The Phenotype Of Bd Based On Prsmentioning
confidence: 60%
“…Twelve of the differentially methylated regions identified in the former study overlapped with the loci identified by a GWAS of bipolar disorder (Stahl et al, 2019). The polygenic risk score derived from GWAS was used to explore the genetic risk of bipolar disorder (Biere et al, 2020). In addition, despite the lack of clear evidence from GWAS linking bipolar disorder to circadian rhythm disruption (Walker et al, 2020) or any of the clock genes (McCarthy, 2019) in humans, research on this topic is growing.…”
Section: Discussionmentioning
confidence: 99%